2015
DOI: 10.1111/iep.12114
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of four different B16 murine melanoma cell sublines: C57BL/6J skin

Abstract: Transplantable murine melanomas are well-established models for the study of experimental cancer therapies. The aim of this study was to explore the behaviour of four different B16 murine melanoma cell sublines after inoculation into C57BL/6J mice; and, more specifically to analyse skin changes, with respect to two specific parameters: clinical (tumour volume, melanin amount, erythema) and histological (H & E, S100, VEGF expression). Both non-invasive and invasive analysis showed that B164A5 is the most aggres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…In a study of Danciu et al . (2015), the authors also have observed an increase of melanin in B16-F10 melanoma tumor subcutaneously injected into the flank [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of Danciu et al . (2015), the authors also have observed an increase of melanin in B16-F10 melanoma tumor subcutaneously injected into the flank [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…On account of our group expertise in the field of skin pathologies (Dehelean et al, 2013, 2016; Gheorgheosu et al, 2013; Soica et al, 2014; Danciu et al, 2015), the present study could be seen as a first step in the synthesis and characterization of the magnetic iron nanoparticles double coated with oleic acid as future carrier platforms for transdermal drug delivery in skin malignancies (melanoma and non-melanoma skin cancers, auto-immune diseases—epidermolysis bullosa acquisita). In this regard was evaluated the toxicological profile of the colloidal suspensions on human keratinocytes cell line and by applying the dermal acute test to SKH-1 hairless mice.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that a screening of the number of chemotherapeutic agents, in relation to their source, concludes that over 60% of approved drugs are derived from natural molecules. Vincristine, vinblastine, paclitaxel, docetaxel, topotecan, and irinotecan are only some examples of important plant-derived anticancer agents [ 6 , 7 ]. Among the phytochemicals with anticancer properties, flavonoids represent one of the most studied classes of natural compounds [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%